Clinical and cerebrospinal fluid findings contribute to the early differentiation between infectious and noninfectious encephalitis - Wilken, Miguel (2017)
Early recognition and prompt specific treatment are crucial factors influencing the outcome of pa- tients with acute encephalitis. The aim of this study was to determine the main causes of acute encephalitis in our population and to find predictors that may lead to specific diagnosis. Adult patients admitted to our hospital with suspected diagnosis of encephalitis in the period 2006-2013 were included. One hundred and five medical records were analyzed. Eighty-two patients with infectious encephalitis were identified (78% of total cases), 53 (65%) men and 29 (35%) women, mean age 47.8 years. The most common microorganisms identi- fied were: HSV-1 (11%), VZV (10%), HSV-2 (5%) and EBV (5%). Twenty-three patients (22% of the series) had non-infectious encephalitis. Headache (p < 0.0001) and fever (p = 0.008) were more frequent in encephalitis of infectious origin. Protein levels and white blood cell counts in the cerebrospinal fluid were significantly higher in patients affected by infectious encephalitis than in those affected by noninfectious encephalitis (OR 95% CI 12.3 [2.9-51.7] and OR 95% CI 7.4 [2-27], respectively). Identifying specific causal agents of acute encephalitis remains a major challenge. Cerebrospinal fluid markers, as well as specific clinical findings, may however contribute toinitial differentiation between infectious and noninfectious causes.